Assessing motor impairment after stroke: a pilot reliability study. Issue 7 (July 1990) - Collin, C; Wade, D
Abstract : Two short tests of motor function, the Motricity Index (MI) and the Trunk Control Test (TCT), were assessed at regular intervals after stroke and compared with a detailed physiotherapy test, the Rivermead Motor Assessment (RMA). The MI and TCT were valid and reliable tests which were usually quicker to perform than the RMA. The TCT was of predictive value when related to eventual walking ability. All three tests appeared to be of equal sensitivity in detecting change.